An Exploration of the Social Brain Hypothesis in Insects - Lihoreau, Mathieu; Latty, Tanya; Chittka, Lars (Frontiers in Physiology, 2012)
The ‘social brain hypothesis’ posits that the cognitive demands of sociality have driven the evolution of substantially enlarged brains in primates and some other mammals. Whether such reasoning can apply to all social animals is an open question. Here we examine the evolutionary relationships between sociality, cognition and brain size in insects, a taxonomic group characterized by an extreme sophistication of social behaviors and relatively simple nervous systems. We discuss the application of the social brain hypothesis in this group based on comparative studies of brain volumes across species exhibiting various levels of social complexity. We illustrate how some of the major behavioral innovations of social insects may in fact require little information processing and minor adjustments of neural circuitry, thus potentially selecting for more specialized rather than bigger brains. We argue that future work aiming to understand how animal behavior, cognition and brains are shaped by the environment (including social interactions) should focus on brain functions and identify neural correlates of social tasks, not only brain sizes.